Prone positioning may increase lung overdistension in COVID-19-induced ARDS - Michal Otáhal; Mikuláš Mlček; João Batista Borges; Glasiele Cristina Alcala; Dominik Hladík; Eduard Kuriščák; Leoš Tejkl; Marcelo Amato; Otomar Kittnar (Scientific Reports, 2022)
Abstract Real-time effects of changing body position and positive end-expiratory pressure (PEEP) on regional lung overdistension and collapse in individual patients remain largely unknown and not timely monitored. The aim of this study was to individualize PEEP in supine and prone body positions seeking to reduce lung collapse and overdistension in mechanically ventilated patients with coronavirus disease (COVID-19)-induced acute respiratory distress syndrome (ARDS). We hypothesized that prone positioning with bedside titrated PEEP would provide attenuation of both overdistension and collapse. In this prospective observational study, patients with COVID-19-induced ARDS under mechanical ventilation were included. We used electrical impedance tomography (EIT) with decremental PEEP titration algorithm (PEEPEIT-titration), which provides information on regional lung overdistension and collapse, along with global respiratory system compliance, to individualize PEEP and body position. PEEPEIT-titration in supine position followed by PEEPEIT-titration in prone position were performed. Immediately before each PEEPEIT-titration, the same lung recruitment maneuver was performed: 2 min of PEEP 24 cmH2O and driving pressure of 15 cmH2O. Forty-two PEEPEIT-titration were performed in ten patients (21 pairs supine and prone positions). We have found larger % of overdistension along the PEEP titration in prone than supine position (P = 0.042). A larger % of collapse along the PEEP titration was found in supine than prone position (P = 0.037). A smaller respiratory system compliance was found in prone than supine position (P < 0.0005). In patients with COVID-19-induced ARDS, prone body position, when compared with supine body position, decreased lung collapse at low PEEP levels, but increased lung overdistension at PEEP levels greater than 10 cm H2O. Trial registration number: NCT04460859.